2018
DOI: 10.1111/jopy.12394
|View full text |Cite
|
Sign up to set email alerts
|

Do psychopathic birds of a feather flock together? Psychopathic personality traits and romantic preferences

Abstract: Relative attraction to psychopathic males and observed homophily may be avenues through which psychopathic traits persist in the population across time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 69 publications
1
4
0
1
Order By: Relevance
“…The goal of Study 2 (main study) was to investigate potential differences in predictors for romantic attraction to villains and heroes. We found that women are more romantically attracted to heroes than villains, which is in line with previously mentioned findings from prior research ( 30 , 31 , 35 , 40 , 43 ), but also with the pilot study. These findings occurred even despite our efforts to reduce potentially perceived self-threat by using pictures of fictional characters ( 44 ), and attempts to include approximately equally handsome TV characters based on the pilot study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The goal of Study 2 (main study) was to investigate potential differences in predictors for romantic attraction to villains and heroes. We found that women are more romantically attracted to heroes than villains, which is in line with previously mentioned findings from prior research ( 30 , 31 , 35 , 40 , 43 ), but also with the pilot study. These findings occurred even despite our efforts to reduce potentially perceived self-threat by using pictures of fictional characters ( 44 ), and attempts to include approximately equally handsome TV characters based on the pilot study.…”
Section: Discussionsupporting
confidence: 92%
“…However, other studies have shown that people are generally not attracted to people with maladaptive personality traits ( 31 , 43 ). Likewise, despite the greater attraction to dark personality traits in young women compared to older women, they preferred men with less dark personality traits ( 35 ).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…To date, research has revealed many features of antagonism-related personality constructs that might underlie their self-perpetuating nature. Some of this research has focused on an insensitivity to distress or fear cues in others (Blair et al, 2001; Lykken, 1995), lack of self-control (Vazire & Funder, 2006), inability to suppress dominant response tendencies (Patterson & Newman, 1993; see also Jonason et al, 2018), hostility or misanthropy (Jones & Neria, 2015), aberrant preferences (e.g., enjoying watching others become aggravated, enjoying danger; Buckels et al, 2019), misunderstanding of social norms (Hart et al, 2019), misgauging other’s perspectives and preferences (Hart, Breeden, & Richardson, 2020; Hart et al, 2016; Miao et al, 2019; Tortoriello & Hart, 2019), homophily and tendencies to exist in social environments that compel and reinforce antagonism (Hart & Adams, 2014; Lavner et al, 2015; Watts et al, 2019), and the strategic presentation of socially undesirable self-images to influence audiences in desired ways (e.g., use of intimidation to gain power; Hart et al, 2017; 2019; Jonason & Webster, 2012). Although these features are distinguishable, they can arguably all be grouped into three broader explanatory categories.…”
mentioning
confidence: 99%
“…2010 yılında yapılan bir çalışmada 24 ise, obsesif kompulsif ve histriyonik kişilik bozukluklarının güvenilirlik katsayılarının düşük olması nedeniyle envanter revize edilerek bu iki alt ölçek için DSM'nin ilk dört ve altıncı ölçütleri kullanılmıştır. SCATI, psikopati ve sınır kişilik bozukluğu, 25 içsel ve dışsal motivasyon, 26 yaşlılarda kişilik bozuklukları, 27 Horney'in psikodinamik yaklaşımı ve kişilik bozuklukları, 28 duygusal zeka, kişilik bozuklukları ve sahne sanatları, 29 psikopatik kişilik özellikleri ve romantik tercihler, 30 profesyonel aktörlerin kişilik bozuklukları profillerinin araştırılması 31 gibi birçok çalışmada kullanılmıştır.…”
Section: Bilge 15unclassified